1992
DOI: 10.1136/sti.68.5.294
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pediculosis pubis and scabies.

Abstract: Conclusion-In this setting scabies appears to be determined by socioeconomic factors and pediculosis pubis predominantly by sexual activity factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…As noted in previous studies 6,7 , we also observed a preponderance of males with scabies infestation with a male-to-female ratio for scabies infestation of 45 to 2 in the GUM clinic patients. Although the reasons for this gender difference are unknown, it may be because women see their family doctors or treat themselves rather than attending a GUM clinic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As noted in previous studies 6,7 , we also observed a preponderance of males with scabies infestation with a male-to-female ratio for scabies infestation of 45 to 2 in the GUM clinic patients. Although the reasons for this gender difference are unknown, it may be because women see their family doctors or treat themselves rather than attending a GUM clinic.…”
Section: Discussionsupporting
confidence: 89%
“…A study by Hart showed an association between scabies and socioeconomic factors 7 . There was no association observed between scabies and factors such as no steady partner, multiple partners and homosexual behaviour in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Scabies and pediculosis are parasitic diseases spreading easily in confinement conditions [ 8 , 9 , 12 , 13 , 14 , 15 ]. In 2008–2015 in Poland, there were on average 82,708 prisoners in penitentiary institutions; scabies and pediculosis were diagnosed in 2.3% and 1.9% of the total number of prisoners, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 12 13 ] Phthiriasis pubis was reported by Bignell in 2% and Hart reported 1.1% in their studies. [ 14 15 ]…”
Section: Discussionmentioning
confidence: 99%